Legal Journal "Examination of the Judge's Decision in the Acts of Online Football Gambling" (Case study 2864 / Pid.B / 2019 / PN.sby) - Diki Wendyanto; Endah Lestari Dwirokhmeiti (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
The Criminal Code (KUHP) has criminal rules outside of the Law, namely Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), in the world of sports the name football is one of the most famous sports games where -where. In the world of football, players are familiar with good gambling. football or the audience and even the referee as a court also participates in a gamble, but in principle playing gambling as stipulated in Article 303 of the Criminal Code (KUHP) and Article 27 paragraph (2) of the ITE Law. appropriate in its application to the Surabaya Court Decision number2864 / Pid.B / 2019 / PN sby regarding the Crime of Online Gambling from the probleman the writer can formulate the problem namely What is the decidendi ratio for the High Court Decision Number 2864 / Pid.B / 2019 / PN sby? and Is the application of the judge's decision on Decision 2864 / Pid.B / 2019 / PN sby in accordance with the elements of material criminal law? The method used by the author is a normative type with a statutory approach, conceptual, case analysis. In this verdict, it turned out that the judge was not careful about his judgment.This is related to the indictment of the Public Prosecutor who only accused the defendant under Article 303 Paragraph (1) 2nd. In fact, when the indictment does not meet the requirements for an accurate, clear and complete description, the indictment letter will be null and void.